Islam and gender in the boundary work of young adults in Switzerland - Dahinden, Janine (My University, 2012)
In many European countries, cultural and religious diversity is increasingly discussed as being a fundamental problem. This paper addresses this issue by applying the theoretical perspective of boundary work: On behalf of a mixed-method-study with young adults, we explore how public discursive constructions about ‘differences’ are used and interpreted in daily life in order to constitute groups and define the boundaries between them. The data shows that a majority (Swiss and second generation youth of Italian, Spain, French or Portuguese origin) constructs a bright boundary against ‘Muslims’ by mobilizing specific ideas about religious practices and by underpinning them with gender equality arguments. The Muslim minority youth are not able to tackle this boundary because of its bright nature; therefore, they develop individual strategies of repositioning within this stratified boundary system. We argue that in this transnationalized context established forms of domination emerge based on the intersection of religion and gender.
Keywords: Boundary work; Religion; Gender; Muslims; Switzerland; Transnationalism